G 30 PROJECT : INTERNASIONALISASI PENDIDIKAN TINGGI DI JEPANG - Arsi Widiandari (IZUMI, 2018)
Internationalization of Japanese Higher Education is not a new issue, but has begin since 1983. In 1983, the Japanese Government lead by Prime Minister Nakasone Yasuhiro announced its plan to accept 100.000 international students by 2000. The target number of international student was reached in 2003. In 2008, Japanese Government announced new plan to accept 300.000 international students by 2020. This plan called Global 30 or Ryuugakusei 30-mannin keikaku. To achieve this target, thirteen universities has been chosen to be pilot for the project. One of main aim of Global 30 is to develop system where student can learn in international method, so some university offer English program by invite English speaker lecturer, and English training for university’s staff. This paper reviews the internationalization of Higher Education in Japan, focus on Global 30 project. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor